2009
DOI: 10.1097/psy.0b013e3181ac9bce
|View full text |Cite
|
Sign up to set email alerts
|

Joint Modeling of Longitudinal Changes in Depressive Symptoms and Mortality in a Sample of Community-Dwelling Elderly People

Abstract: Objective-Research on the relationship of depression to mortality has yielded mixed results. Limitations of previous studies include mostly one-time assessment of depression, short follow-ups, and failure to model changes in depression appropriately. We attempted to use a joint modeling approach to examining the association between longitudinal changes in depressive symptoms and mortality.Methods-Data were obtained from the Florida Retirement Study, a prospective cohort study of community-dwelling oldest old i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
43
4
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(57 citation statements)
references
References 65 publications
(93 reference statements)
9
43
4
1
Order By: Relevance
“…The overaU larger risk found for severe depression than for moderate symptoms (Rozzini et al 2001;GeerUngs et al 2002;Sehoevers et al 2009;St John & Montgomery, 2009;Zhang et al 2009), the sUghtly reduced effects for women (Saz & Dewey, 2001 ;Anstey & Luszcz, 2002;Sehulz et al 2002;Barry et al 2008) and for longer foUow-up periods (Saz & Dewey, 2001;Zhang et al 2009) are aU comparable to those reported in previous studies. In addition, our findings suggest that changes in severity of symptoms occurring over a 3-year interval are powerful and signifieant predictors of 7-year mortaUty, even after eontroUing for a comprehensive set of potentially eonfounding faetors, leading to a 37-44% reduction in risk in subjeets with transition to a better status, and to a 34-46% exeess "=MHR (95% CI) based on a Cox regression model adjusting for other covariates selected through a forward stepwise selection approach.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The overaU larger risk found for severe depression than for moderate symptoms (Rozzini et al 2001;GeerUngs et al 2002;Sehoevers et al 2009;St John & Montgomery, 2009;Zhang et al 2009), the sUghtly reduced effects for women (Saz & Dewey, 2001 ;Anstey & Luszcz, 2002;Sehulz et al 2002;Barry et al 2008) and for longer foUow-up periods (Saz & Dewey, 2001;Zhang et al 2009) are aU comparable to those reported in previous studies. In addition, our findings suggest that changes in severity of symptoms occurring over a 3-year interval are powerful and signifieant predictors of 7-year mortaUty, even after eontroUing for a comprehensive set of potentially eonfounding faetors, leading to a 37-44% reduction in risk in subjeets with transition to a better status, and to a 34-46% exeess "=MHR (95% CI) based on a Cox regression model adjusting for other covariates selected through a forward stepwise selection approach.…”
Section: Discussionsupporting
confidence: 85%
“…It has been argued that different lengths of exposure to depression may affect the association with mortality beeause with a longer duration the negative effeets on both biologieal and psyehosoeial functioning should have more time to accumulate (Sehoevers et al 2009). OveraU, the results of previous studies suggest that long-standing depression prediets mortaUty even after eontroUing for possible eonfounding faetors (Pulska et al 1999) and that both severity and persistenee of depression are associated with a higher mortality risk (GeerUngs et al 2002;Sehoevers et al 2009;Zhang et al 2009;Bogner et al 2011). Aeeording to the few studies analyzing gender differenees, changes in depressive status, and in incident depression in partieular, are associated with all-cause (Anstey & Luszcz, 2002) and cardiovascular disease mortaUty (Penninx et al 1998) only for elderly men, whereas the higher burden of depression in women may be attributable to a greater suseeptibUity to depression, a higher persistenee of the eondition and a lower probabUity of death (Barry et al 2008).…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…However, in contrast to the 11 yearly assessments in the Florida Retirement Study (Zhang et al, 2009), the intervals between the five waves of our longitudinal study were uneven and more widely spaced in later waves. Past findings indicate a curvilinear pattern of age-related changes in depressive symptoms (Clarke et al, 2011) and abrupt changes in life satisfaction and affective well-being at about 4-7 years before death Gerstorf et al, 2010;Schilling et al, 2012).…”
Section: Limitations and Outlookcontrasting
confidence: 66%
“…joining the multilevel model and survival model (Rizopoulos, 2012). For example, joint modeling has been fruitfully applied in the examination of the association between longitudinal changes in cognitive functioning and mortality (Ghisletta, 2008;Ghisletta, McArdle, & Lindenberger, 2006;Graham et al, 2011).Recently, joint modeling has been applied to data from the Florida Retirement Study.Results indicate that an increase in depressive symptoms over 11 years was associated with higher mortality rates in older adults (Zhang et al, 2009). Specifically, using time-in-study as the time metric, an annual increase of one point in depressive symptoms was associated with a 1.57-fold increase in mortality, controlling for baseline covariates including age, gender, education, marital status, living arrangement, cognitive functioning, and illness burden.…”
mentioning
confidence: 86%